Clinical efficacy of native drug Adgelon in knee osteoarthritis - R M Balabanova; I B Vinogradova; O N Ivanova; A K Kaptaeva; R S Saikovsky; V N Sorotskaya; N M Tereshenko; N V Chichasova; S S Yakushin (Научно-практическая ревматология, 2009)
Results of treatment of 76 pts with knee osteoarthritis with native drug Adgelon (glycoprotein possessing biological activity at super low doses) are presented. WOMAC index, Lequesne functional index and SF-36 questionnaire show analgesic effect and quality of life improvement after 6 intra-articular adgelon injections during 3 weeks. Subsequent follow up for 2 months revealed aftereffect of the drug.